Can fiddler crabs detect underwater predators? A laboratory test with Leptuca thayeri. Issue 1 (2nd January 2019) - De Grande, Fernando Rafael; Cannicci, Stefano; Costa, Tânia Marcia
Abstract : Fiddler crabs are intertidal organisms well known to be highly adapted to low tide activity, thus a number of researches have studied their physiological, behavioral and sensory adaptations to such a tidal phase. However, recent evidences showed that some fiddler crabs are the main food item of fish, suggesting that they could also be active underwater. Based on these preliminary observations, we designed laboratory trials aimed to investigate the ability to detect underwater predators in Leptuca thayeri, across sexes and life stages. We tested a combination of chemical and visual cues, using the predator fish Sphoeroides greeleyi, and, as a control, the non-predator fish Mugil curema. Leptuca thayeri detected the presence of chemical cues coming from the predator fish, although significant differences between adults and juveniles were observed. Adults of L. thayeri remained within their burrows and avoided predator exposition, while juveniles were bold and even increased their activity on the sediment surface. We suggest that juvenile crabs' boldness could be explained by a predator inspection behavior, which allows them to gather information about the possible risk of different predatory species, while experienced adults reduce predation risk recognizing the predator itself.